Analisis Perbedaan Cadangan Endapan Bijih Nikel Saprolit antara Hasil Eksplorasi dan Realisasi Penambangan pada Blok Penambangan Pulau Gee - Triyanto, Bambang; Patimah, Ai Siti (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
This study is part of mining exploration activities, which are crucial to ensure the accuracy of reserve estimates in order to support effective production planning. This is particularly important given the frequent discrepancies between exploration data and actual mining realization. Therefore, a detailed analysis is required to identify the factors causing tonnage deviations in saprolite nickel ore deposits. This study aims to analyze the differences between saprolite nickel ore deposit reserves from exploration results and mining realization at the Gee Island Mining Block and identify the factors influencing these discrepancies. The method used is the area of influence approach, where reserve calculations are based on determining the boundary areas around drill holes, covering half of the area between adjacent drill holes. The mining system applied is an open-pit mine with a mining recovery rate of 90%. The results show that the mined nickel ore tonnage in July was 20,161 tons from exploration, with an actual production tonnage of 19,432 tons, while in August, the exploration tonnage was 25,603 tons, with an actual production tonnage of 24,410 tons. The percentage of tonnage deviation reached 3.62% in July and 4.66% in August. Several factors were identified as causes of tonnage reduction, including drilling spacing and recovery, preparation process, ore extraction technique, and the applied reserve calculation method.